Review of COVID-19 Myocarditis in Competitive Athletes: Legitimate Concern or Fake News? - Khan, Zulqarnain; Na, Jonathan S.; Jerome, Scott (Frontiers in Cardiovascular Medicine, 2021)
Since the first reported case of COVID-19 in December 2019, the global landscape has shifted towards an unrecognizable paradigm. The sports world has not been immune to these ramifications; all major sports leagues have had abbreviated seasons, fan attendance has been eradicated, and athletes have opted out of entire seasons. For these athletes, cardiovascular complications of COVID-19 are particularly concerning, as myocarditis has been implicated in a significant portion of sudden cardiac death (SCD) in athletes (up to 22%). Multiple studies have attempted to evaluate post-COVID myocarditis and develop consensus return-to-play (RTP) guidelines, which has led to conflicting information for internists and primary care doctors advising these athletes. We aim to review the pathophysiology and diagnosis of viral myocarditis, discuss the heterogeneity regarding incidence of COVID myocarditis among athletes, and summarize the current expert recommendations for RTP. The goal is to provide guidance for practitioners who will be managing and advising athletes in the COVID era.